PERLINDUNGAN DAN PEMANFAATAN AIR BESIH DIKABUPATEN NGADA - Bendito Mitang, Yohanes; Lobo, Ferdinandus; Arman.Svd, Yohanes; Octavianus Waang, Andre William; Tuku Tiwa, Aprilianus; Gae Soro, Elroswit E. Teresa; Ceriesy Onul Unggas, Frederikus; M.Walep, Imanuel; Marsico Oematan, Bernadio (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Water is one of the renewable natural resources, whose availability and quality are limited and declining, although according to the law of material conservation the amount of water in the world does not change. Water has many functions, such as in the metabolic process water is used by organisms in chemical reactions, it is also a medium for nutrient transport. The purpose of water management is of course accompanied by problems that arise with water. The use of water management in general also has a great impact as a source of clean water suitable for consumption. Proper water management is beneficial in preventing landslides, floods, and land footprints.